2012
DOI: 10.1002/uog.11089
|View full text |Cite
|
Sign up to set email alerts
|

Could antispasmodic drug reduce pain during hysterosalpingo‐contrast sonography (HyCoSy) in infertile patients? A randomized double‐blind clinical trial

Abstract: Objective To assess the effectiveness of an antispasmodic drug, hyoscine-N-butylbromide, in reducing pain during hysterosalpingo-contrast sonography (HyCoSy). Methods

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 40 publications
1
25
0
Order By: Relevance
“…Jareethum et al 45 compared two different analgesic drugs, hyoscine‐N‐butylbromide and mefenamic, versus placebo for pain relief during SHG in a double‐blind RCT. No statistically significant differences were found in pain reduction between the three groups, similar to the results of Moro et al 44.…”
Section: Do Pain Medications Reduce Pain?supporting
confidence: 90%
See 1 more Smart Citation
“…Jareethum et al 45 compared two different analgesic drugs, hyoscine‐N‐butylbromide and mefenamic, versus placebo for pain relief during SHG in a double‐blind RCT. No statistically significant differences were found in pain reduction between the three groups, similar to the results of Moro et al 44.…”
Section: Do Pain Medications Reduce Pain?supporting
confidence: 90%
“…Although it has been found that women better tolerate SHG and HyCoSy compared to HSG41, 42, 43, should we expect painkillers to significantly reduce pain during SHG and HyCoSy or will there be no effect, as with HSG? In a large double‐blind RCT in this issue of the Journal, Moro et al 44 demonstrated no significant pain reduction with an antispasmodic drug compared with placebo in patients undergoing HyCoSy with 30 mL 1 : 1 saline and air. In this study, 816 patients undergoing HyCoSy were randomized to receive 10 mg hyoscine‐N‐butylbromide or placebo.…”
Section: Do Pain Medications Reduce Pain?mentioning
confidence: 99%
“…Inflation of the catheter's balloon induced the nerve fibers of the uterine cervix, leading to pelvic pain and vasovagal response. In addition, local prostaglandins release (due to of the uterine expansion) caused uterine cramps and pain [25]. In our study, we found that inflating the balloon inside the uterine cavity was more painful and could result in a larger number of vasovagal reactions.…”
Section: Discussionmentioning
confidence: 61%
“…Although convincing, this hypothesis has been disconfirmed by a recent study. In fact it was demonstrated that a preventive administration of antispasmodic drug such as hyoscine-N-butylbromide, a muscarinic receptor antagonist with anticholinergic effects, does not decrease pain during HyCoSy by affecting uterine contractions [23]. …”
Section: Discussionmentioning
confidence: 99%